Safety of perioperative intravenous different doses of dexamethasone in primary total joint arthroplasty: a retrospective large-scale cohort study - Ping Mou; Xiao-Dan Zhao; Xiu-Mei Tang; Zun-Han Liu; Hao-Yang Wang; Wei-Nan Zeng; Duan Wang; Zong-Ke Zhou (BMC Musculoskeletal Disorders)
Abstract Purpose Perioperative intravenous different doses of dexamethasone (DEX) can realize effective clinical outcomes in total joint arthroplasty (TJA). However, the effect of different DEX doses on readmission rates and postoperative complications remains unclear. Methods We retrospectively analyzed patients who underwent primary TJA between December 2012 and October 2020. Patients were categorized into three groups based on the total perioperative dose of DEX: control group (DEX = 0 mg), low-dose group (DEX < 15 mg), and high-dose group (DEX ≥ 15 mg). Primary outcomes included 30-day and 90-day readmission rates. Secondary outcomes included the rates of periprosthetic joint infection (PJI) and wound complications, with treatment outcomes for these complications were also evaluated. Multivariable analysis was used to identify risk factors for readmission. Results A total of 14,557 procedures were included, with 6,686 in the control group, 4,325 in the low-dose group, and 3,546 in the high-dose group. No significant differences were observed among the groups for 30-day (p = 0.645) or 90-day readmission rates (p = 0.539). Additionally, there were no significant differences in rates of PJI (p = 0.401) or wound complications (p = 0.079). Treatment for PJI and wound complications was successful across all groups. Risk factors for 30-day readmission included age > 80 years (OR: 2.585, 95% CI: 1.123–5.954, p = 0.026) and undergoing total hip arthroplasty (THA) (OR: 1.692, 95% CI: 1.137–2.518, p = 0.009). For 90-day readmission, age 71–80 years (OR: 2.199, 95% CI: 1.349–3.583, p = 0.002), age > 80 years (OR: 3.897, 95% CI: 1.966–7.727, p < 0.001), and THA (OR: 1.622, 95% CI: 1.179–2.230, p = 0.003) were significant risk factors. However, neither low-dose nor high-dose DEX was associated with increased 30-day or 90-day readmission rates. Conclusions Perioperative intravenous DEX may be not associated with the readmission, PJI, and wound complications in patients undergoing primary TJA.